2021
DOI: 10.21203/rs.3.rs-594347/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Resistance of Peanut to Soil-Borne Pathogens Improved by Rhizosphere Probiotics Under Calcium Treatment

Abstract: Background: Peanut (Arachis hypogaea L.) is an important oil and economic crop. Calcium can regulate plant autoimmunity, respond to biotic and abiotic stresses, and improve plant resistance to pathogens. The enrichment of beneficial microorganisms in the rhizosphere is related to plant disease resistance and soil development. The purpose was to analyze the differences of peanut rhizosphere microbial community structure between calcium treatment and control during two growth stages, and the reason that calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Li et al found that both embryo and red skin of peanut seed need to absorb Ca 2+ that's excreted from the shell to ensure pod growth and development, and that peanut seed development was regulated by the collaboration of Ca 2+ signal transduction and hormone regulation pathway [8]. Zhang et al also found that calcium application could improve disease resistance to soil-borne pathogens by enriching them with speci c dominant bacteria [9]. Chen et al identi ed that multiple signal pathways involved in embryo abortion under calcium de ciency, which induced increased IAA and ethylene but decreased ABA, gibberellin, cytokinin and brassinosteroid levels [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al found that both embryo and red skin of peanut seed need to absorb Ca 2+ that's excreted from the shell to ensure pod growth and development, and that peanut seed development was regulated by the collaboration of Ca 2+ signal transduction and hormone regulation pathway [8]. Zhang et al also found that calcium application could improve disease resistance to soil-borne pathogens by enriching them with speci c dominant bacteria [9]. Chen et al identi ed that multiple signal pathways involved in embryo abortion under calcium de ciency, which induced increased IAA and ethylene but decreased ABA, gibberellin, cytokinin and brassinosteroid levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the global view of peanut transcriptome under calcium de ciency, previous studies only reported differentially expressed genes (DEGs) between calcium de cient and su cient conditions in the same cultivar [4,6,[8][9][10], and few of them made comparisons between different cultivars with different seed size, which showed tolerance inconsistency under calcium de ciency. The pod fullness was reported to be in uenced by seed calcium concentration, which is affected by seed size, absorption ability of cultivars and soil calcium fertility during seed development stage [16].…”
Section: Introductionmentioning
confidence: 99%